Publications in 2024 and reviewers in 2021 - 2024 on Clinical Critical Care and indexing in Thai-Journal Citation Index - Tier 1 (valid 2025 - 2029): Publications, reviewer and TCI Tier-1 - Chittawatanarat, Kaweesak; Rungruanghiranya , Suthat (Clinical Critical Care, 2025)
In its 33rd year of publication under the Thai Society of Critical Care Medicine and entering its 5th year as Clinical Critical Care, the journal has reached another milestone by being indexed in the Thai-Journal Citation Index (TCI) Tier 1. This editorial will highlight the published works of the journal, along with expert reviews from various fields, whose insights and critiques have contributed to refining and enhancing the quality of the published research.